An indoor evacuation guidance system with an AR virtual agent - Gan, Quehong; Liu, Zhen; Liu, Tingting; Chai, Yanjie (Procedia computer science, 2022)
It is challenging to evacuate people quickly and safely in large complex buildings in emergencies. With the rapid development of smart mobile devices, the research of augmented reality (AR) technology in emergency evacuation is gradually becoming a hot topic. Meanwhile, virtual agents have been widely used in numerous fields and have been proved to be helpful for guidance. Therefore, this study proposes an indoor evacuation guidance system with an AR virtual agent. The system uses smartphones as mobile terminals to deliver optimal exit path directions for users in real-time. An AR virtual agent is used to guide users to evacuate quickly and safely in complex building environments. In this paper, we take a museum as an example and use the permanent features in the museum as markers for the AR application to activate the virtual agent, which plays the role of a guide to help users evacuate the building. This paper describes the design and implementation of the system, and conducts a user study at a local museum to evaluate the system's usability. The results show that the system can effectively provide guidance and help users to evacuate indoors in the emergency.